Interfund lending in mutual fund families: Role of internal capital markets - Vikas Agarwal; Haibei Zhao (University of Cologne, Centre for Financial Research (CFR), 2016)
Although the 1940 Act restricts interfund lending within a mutual fund family, families can apply for exemptions from the regulator to participate in interfund lending. We find that heterogeneity in portfolio liquidity and investor flows across funds, funds' investment restrictions, and governance mechanisms determine the applications for interfund lending. We document several costs and benefits of interfund lending after the application. Costs include lower sensitivity of managers' turnover to past performance and greater investor withdrawal for poorly governed funds. Benefits include funds holding more illiquid and concentrated portfolios, and being less susceptible to runs. Finally, well-governed funds perform better.
Keywords: G18; G23; G32; 330; funding liquidity; fund families; internal capital markets; fund performance